Metaphorical Toponyms of Present-Day Vilnius County: Extending Toponymy Research through Cognitive Metaphor Theory: Topónimos metafóricos del actual condado de Vilnius: extendiendo la investigación mediante la Teoría de la Metáfora Cognitiva - Skorupa, Pavel (Onomástica desde América Latina, 2025)
Taking present-day Vilnius County, which marks the cultural and linguistic periphery, as a case study, the attempt is made in this paper to expand the horizons of traditional onomastic research by introducing Cognitive Metaphor Theory (CMT) as an innovative approach to understanding the motivation of toponyms. Onomastic research has traditionally focused on toponyms’ etymology, derivation, and historical context. In contrast, this article explores how the application of CMT enhances our understanding of the cognitive processes inherent in toponymy. In this way, this study contributes to advancing the disciplinary field of cognitive onomastics by providing insights into how language and cognition intertwine in the conceptualization and naming of geographical features. Rooted in cognitive linguistics, CMT assumes that abstract concepts are often understood and structured through metaphors derived from tangible experiences. In the context of toponymy, this research investigates how place names are not merely linguistic labels for geographic locations but are inherently linked to cognitive structures and mental representations. CMT facilitates our understanding of toponyms’ linguistic and historical dimensions and uncovers the cognitive processes underlying their creation and interpretation. By bridging the traditional onomastic research with a cognitive approach, this novel perspective offers a deeper insight into the complex interplay of language, cognition, and geographical space. The analysis integrates traditional onomastic research methods with Cognitive Onomastics principles, utilizing frameworks from both Lithuanian and foreign scholars to classify selected Vilnius County toponyms through etymological, derivational, and semantic analyses, while also examining associated extralinguistic data. The analysis found that metaphorical toponyms in Vilnius County, though relatively uncommon, carry symbolic or cultural meaning. A total of 38 metaphorical names were identified among limnonyms, potamonyms, and oikonyms, highlighting their role in depicting the interplay between language, culture, and the environment.